PENERAPAN MODEL SIMULASI PENJADWALAN ANTRIAN NASABAH BANK MEGA PADANG - Firdalius, Fitri (Sainstek : Jurnal Sains dan Teknologi, 2017)
Along with progress in improving communication and information, more people who gather as much information as possible through various media had. But not everyone is able to manage information to good use at the appropriate time efficiently and effectively. Because it has a lot of information alone is not sufficient if it can not manage to become the best alternative using the simulation system model of scheduling customers in a bank queue. With the design of simulation models the scheduling queue is expected to provide customers get into the parties will try to develop a simulation, so it can be seen every error that occurs during the development of models and simulations. The design of this system using excel simulation tests, with the implementation of systems using Microsoft Access 2003 database system and program visual basic 6.0. From system design are made to dipe.